Ion removal effect by soil remediation and desalination - Chendi Shi; Haozhe Wang; Yuxuan Li; Mingxiang Xu; Xilian Luo (PLoS ONE, 2026)
Electrokinetic remediation of saline soils currently faces two primary constraints: high energy consumption and considerable variability in the removal efficiency of salts and base ions under differing treatment conditions. These limitations have hindered the widespread practical adoption of this technology.This study explores the Ion removal effect by soil remediation and desalination. Through laboratory simulations, the base ion removal effects and energy consumption under various electric field conditions were investigated. The results show that electrokinetic remediation at 2.0 V/cm can effectively remove base ions from the soil, with notable removal efficiencies of Na + and Cl - . It was also found that the electric field strength significantly affects both the remediation effect and energy consumption. An excessively high electric field strength may lead to a sharp decrease in soil moisture content, which in turn affects the remediation efficiency and increases energy consumption. Electrokinetic remediation has considerable potential for improving saline soils. By optimizing the electric field conditions and controlling pH levels, remediation can be enhanced while energy consumption is reduced. However, in practical applications, factors such as soil type and pollution degree must be considered, and further in-depth research is needed to refine and optimize remediation technology.